Dual Action Antimicrobial Surfaces: Alternating Photopatterns Maintain Contact‐Killing Properties with Reduced Biofilm Formation. Issue 10 (16th August 2020) - Blackman, Lewis D.; Fros, Marion K.; Welch, Nicholas G.; Gengenbach, Thomas R.; Qu, Yue; Pasic, Paul; Gunatillake, Pathiraja A.; Thissen, Helmut; Cass, Peter; Locock, Katherine E. S.
Abstract: Contact‐killing antimicrobial coatings are important for reducing medical device related nosocomial bacterial infections, yet they inadvertently suffer from rapid bacterial colonization. To lessen the extent of biofilm formation on such surfaces, it is hypothesized that coatings containing alternating regions of a low‐fouling polymer incorporated into a contact‐killing surface would reduce bacterial colonization, while still allowing for the contact‐killing properties to be retained. To this end, photopatterned surfaces are developed with alternating regions comprised of a crosslinked low‐fouling zwitterionic copolymer and regions containing the antimicrobial peptide nisin for contact‐killing. The surfaces are characterized by X‐ray photoelectron spectroscopy and water contact angle measurements and assessed for their efficacy against Staphylococcus epidermidis colonization. The dual antimicrobial action surfaces present the synergistic advantages of both classes of coatings against the prolific biofilm‐forming bacterium, reducing the biofilm surface coverage by 70% relative to the nonpatterned control, while still retaining their contact‐killing activity. The results suggest that patterned surfaces, which combine nonadhesive regions with contact killing regions, have the potential to provide improved control over bacterial colonization, biofilm formation, and medical device‐associated infections. Abstract : Biofouling of surfaces remains a key issue despite progress in contact‐killing and antiadhesive coatings technology. Alternating low‐fouling polymer regions are installed onto a surface using orthogonal surface modification techniques. These dual action surfaces show significantly reduced biofouling compared to single component contact‐killing surfaces in the presence of a clinically relevant nosocomial opportunistic bacterial pathogen.